2021
DOI: 10.1088/1742-6596/1961/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Traffic signal image detection technology based on YOLO

Abstract: The detection and recognition of traffic signal image is an important content in intelligent transportation system. It can be applied to driver assistance system to effectively recognize traffic signal signs on the road, so as to reduce the occurrence of traffic accidents. At the same time, it also provides strong technical support for the future unmanned driving system. The main content of this paper is based on the deep learning method, using YOLOv3 and YOLOv4 algorithm to detect and recognize the traffic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The depthwise separable convolutional network as a feature extractor achieves an average precision of 97.22% during testing. Zhang Sulan et al [10] used the spectral reflectance of Masson pine as the data source to analyze the ridge trace of 14 spectral characteristic parameters and constructed a pine wilt nematode disease ridge regression monitoring model. The test results showed that the determined coefficient R 2 of the constructed pine wilt nematode ridge regression model was 0.8686, the mean square error RMSE was 0.2735, and the average estimation accuracy was 87.15%, which provides technical support for the early monitoring and control of pine wilt nematode disease.…”
Section: Introductionmentioning
confidence: 99%
“…The depthwise separable convolutional network as a feature extractor achieves an average precision of 97.22% during testing. Zhang Sulan et al [10] used the spectral reflectance of Masson pine as the data source to analyze the ridge trace of 14 spectral characteristic parameters and constructed a pine wilt nematode disease ridge regression monitoring model. The test results showed that the determined coefficient R 2 of the constructed pine wilt nematode ridge regression model was 0.8686, the mean square error RMSE was 0.2735, and the average estimation accuracy was 87.15%, which provides technical support for the early monitoring and control of pine wilt nematode disease.…”
Section: Introductionmentioning
confidence: 99%
“…The alert system is connected to the CPU, which triggers the alarm when animal activity is detected. Data Storage and Management: The system also includes a data storage and management component, which stores all the data captured by the sensors and cameras [9]. The data can be used making, such as identifying patterns of animal activity and optimizing the placement of sensors and cameras.…”
Section: Methodsmentioning
confidence: 99%
“…Target detection based on deep learning has been a research hot spot over the past few years and has aroused wide attention, 1 and relevant technologies have been applied to face recognition, 2 car driverless, 3,4 pedestrian tracking, 5 intelligent transportation, 6 and other fields. Target detection 7 technology has been found as a key technology of Internet of Things in the livestock industry, which is a vital means to monitor the location, number, health status, as well as whether the livestock are in estrus in real time; this technology also lays a basis for achieving intelligent pasture.…”
Section: Introductionmentioning
confidence: 99%